Dynamic Response Analysis of Pile Group Foundation of Super-Giant Sewage Treatment Structure on Hydraulic Fill Foundation - Yi Huang; Xugang Chen; Lijuan Cheng; Tiyong Bai; Ru Yan (Shock and Vibration)
In this study, a 3D numerical model, considering the dynamic interaction between soil, pile foundation, and super structure, and the parameter analysis of internal force response of pile group foundation under differences seismic intensity, was established based on the Bangladesh sewage treatment plant project to investigate the dynamic response of pile group foundation of liquid-containing structures. The results show that the internal force of pile gradually increases with time, and the horizontal dynamic displacement peak value appears earlier under different seismic wave responses and seismic intensity. With the increase of seismic time history, the variation degree of dynamic impedance with frequency and impedance peak will increase. The pile group effect and single pile bearing capacity of foundation in hydraulic fill fine sand and silty clay were verified. By comparing numerical simulation and theoretical calculation, the results show that the pile group foundation exerts the soil squeezing effect after pile construction is completed, and the dynamic elastic modulus of the soil layer can be increased. Simultaneously, the soil layer will have a better integral stiffness. The pile group effect coefficient obtained by the solid perimeter method is most consistent with the numerical simulation method.